PEG-PLA-Coated and Uncoated Radio-Luminescent CaWO4 Micro- and Nanoparticles for Concomitant Radiation and UV-A/Radio-Enhancement Cancer Treatments - Jo, Sung Duk; Lee, Jaewon; Joo, Min Kyung; Pizzuti, Vincenzo J.; Sherck, Nicholas J.; Choi, Slgi; Lee, Beom Suk; Yeom, Sung Ho; Kim, Sang Yoon; Kim, Sun Hwa; Kwon, Ick Chan; Won, You-Yeon (AMER CHEMICAL SOC, 2018)
Currently, there is great interest in the development of ways to achieve the benefits of radiation treatments with reduced negative effects. The present study demonstrates the utilization of radio-luminescent particles (RLPs) as a means to achieve radio-sensitization and enhancement and their ability to affect head-and neck-cancer-cell cultures (in vitro) and xenografts (in vivo). Our approach utilizes a naturally abundant radio-luminescent mineral, calcium tungstate (CaWO4), in its micro or nanoparticulate form for generating secondary UV-A light by gamma ray or X-ray photons. In vitro tests demonstrate that unoptimized RLP materials (uncoated CaWO4 (CWO) microparticles (MPs) and PEG PLA-coated CWO nanopartides (NPs)) induce a significant enhancement of the tumor-suppressive effect of X-rays and gamma rays in both radio-sensitive-and radio resistant-cancer models; uncoated CWO MPs and PEG PLA-coated CWO NPs demonstrate comparable radio-sensitization efficacies in vitro. Mechanistic studies reveal that concomitant CaWO4 causes increased mitotic death in radio-resistant cells treated with radiation, whereas CaWO4 sensitizes radio-sensitive cells to X-ray-induced apoptosis and necrosis. The radio sensitization efficacy of intratumorally injected CaWO4 particles (uncoated CWO MPs and PEG PLA-coated CWO NPs) is also evaluated in vivo in mouse head-and neck-cancer xenografts. Uncoated CWO MPs suppress tumor growth more effectively than PEG PLA-coated CWO NPs. On the basis of theoretical considerations, an argument is proposed that uncoated CWO MPs release subtoxic levels of tungstate ions, which cause increased photoelectric-electron-emission effects. The effect of folic acid functionalization on the in vitro radio-sensitization behavior produced by PEG PLA-coated CWO NPs is studied. Surface folic acid results in a significant improvement in the radio-sensitization efficiency of CaWO4.
Keywords: MONTE-CARLO-SIMULATION; CONCURRENT CHEMORADIOTHERAPY; GOLD NANOPARTICLES; DNA-DAMAGE; RADIOTHERAPY; SENESCENCE; GENOTOXICITY; THERAPY; REPAIR; RADIOSENSITIZATION